On mothering and being mothered: A personal reflection on women's productivity during COVID‐19 - Clancy, Annette (Gend Work Organ, 2020)
This is a personal reflection, as a female academic during COVID‐19, on how women's academic productivity seems primarily to be discussed in relation to a different kind of productivity — motherhood. A recent procedure in a maternity hospital evoked feelings and associations of mothering and being mothered, and how these associations hover over relationships regardless of whether wombs are productive or not. My hope in writing this piece is that every woman's fear and anxiety may be productively contained (regardless of how she is seen from the outside or momentarily construed from within) during this time of extraordinary turmoil.